Original paperHigh-dose-rate interstitial brachytherapy for liver metastases: first study from India - Sharma, Daya Nand; Thulkar, Sanjay; Sharma, Seema; Gandhi, Ajeet Kumar; Haresh, Kunhi Parambath; Gupta, Subhash; Rath, Goura Kisor; Julka, Pramod Kumar (Journal of Contemporary Brachytherapy, 2013)
Purpose : To study the safety and efficacy of high-dose-rate interstitial brachytherapy (HDRIBT) in patients with liver metastases (LM). Material and methods : Between 2009 and 2011, 10 patients with 12 metastatic lesions in the liver were enrolled in this prospective trial. All patients had either refused surgery or found ineligible for surgery due to various factors. Under CT guidance, 16 gauze blind end stainless steel or rigid plastic brachytherapy needle was inserted in the center of lesion through the percutaneous route. Generally, a single interstitial brachytherapy (IBT) needle for lesions up to 3 cm and multiple needles for lesions more than 3 cm in diameter were inserted. Treatment was delivered with a single high-dose-rate (HDR) dose of 20 Gy prescribed to the target. The needles were removed immediately after the treatment. The endpoints of study were acute complications and local control of the disease. Results: The median size of the lesion was 3.8 cm (2.7-7.0 cm). The average time for the entire IBT procedure was 65 minutes (50-105 minutes). Median follow up was 9 months (3-17 months). None of the patients had fatal complications. Minor complications like pain, nausea/vomiting, and asymptomatic pleural effusion were observed in 3, 2 and 1 patients, respectively. Local control rate at 12 months was 75%. The 1-year local progression free survival (LPFS) was 33%. Conclusion : Although limited by small sample size, the results of our first study from India suggest that HDRIBT is a safe and effective non surgical option for LM.